Preventing Criminal Victimization through Community Education: An Islamic Perspective - Hussin, Nasimah; Zawawi, Majdah (2012)
Living and working in a safe area enhances productivity and ensures a safe community. In order to achieve it, crime prevention is considered the main agenda of public authorities. Nevertheless, it has usually been overlooked that the victim him/herself can be the contributing factor to the criminal incident. The key to these problems lies in educating the community on the preventive measures that could be taken in order to avoid victimization of individuals. Such suggestions are based on Islamic principles. This leads to community welfare and the concept of hisbah. Hence, this paper discusses the preventive measures that can be observed by both individuals and the community to prevent criminal victimization.